Thermal analysis of a disc brake model considering a real brake pad surface and wear - Abu Bakar, Abd. Rahim (MechAero Foundation for Technical Research and Education Excellence, MAFTREE, 2010)
Vehicle braking system is considered as one of the most fundamental safety-critical systems in modern vehicles as its main purpose is to stop or decelerate the vehicle. The frictional heat generated during braking application can cause numerous negative effects on the brake assembly such as brake fade, premature wear, thermal cracks and disc thickness variation (DTV). In the past, surface roughness and wear at the pad interface have rarely been considered in studies of thermal analysis of a disc brake assembly using finite element method. This paper attempts to consider these two aspects to predict temperature distributions in a reduced disc brake model. First, two different brake pad interface models, i.e., smooth and rough surfaces are modelled and simulated. Temperature distributions in these two models are then compared. Next, the thermal analysis is performed with the effect of wear at three different braking applications.